A new species of Louisea Cumberlidge, 1994, a freshwater crab from the Ekom-Nkam Waterfall, Cameroon (Brachyura: Potamonautidae: Liberonautinae) - Ndongo, Pierre A. Mvogo; Rintelen, Thomas Von; Clark, Paul F.; Cumberlidge, Neil (Zootaxa, 2025)
A new species of Louisea Cumberlidge, 1994 (Brachyura: Potamonautidae: Liberonautinae) is described from the Nkam River below the Ekom Nkam Waterfalls, near Melong (5.061728°N, 10.030878°E), in the tropical rainforests of Cameroon. The new species is recognized by a unique combination of characters of the carapace, thoracic sternum, and male cheliped, and is supported as a separate lineage by a phylogenetic analysis of species of Louisea based on mtDNA (COI and 16S rRNA). Notes are provided on the ecology and the conservation of L. cataracta sp. nov..